2020
DOI: 10.7759/cureus.9917
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Stem Cell Therapy in Patients With Ischemic Stroke

Abstract: Stem cell therapy is emerging as a promising treatment strategy to treat patients with stroke. While there are established modes of treatment for stroke patients such as thrombolysis and endovascular intervention, most of the stroke patients frequently end up with major residual deficits or even death. The use of stem cells to treat stroke has been found to be beneficial in the animal models but strict evidence for the same in humans is still lacking. We reviewed 13 clinical trials of stem cell therapy in stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This observation is in accordance to the results of the majority of the previous studies, in which most stem cell therapy trials were reported to be safe, aside from their effect on improved functional outcome. [ 12 ] Safety itself is dependent on multiple factors, including the host and the stem cells themselves. Indeed, type, source, dose, route of delivery, and time from onset of stroke to stem cell administration all contribute to the safety and outcome of stem cell therapy in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in accordance to the results of the majority of the previous studies, in which most stem cell therapy trials were reported to be safe, aside from their effect on improved functional outcome. [ 12 ] Safety itself is dependent on multiple factors, including the host and the stem cells themselves. Indeed, type, source, dose, route of delivery, and time from onset of stroke to stem cell administration all contribute to the safety and outcome of stem cell therapy in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…In neurology, ischaemic stroke patients treated with MSCs yielded positive results, whereby the patients showed significantly improved neurological and motor functions (85)(86)(87)(88). Among all of the studies conducted, serious adverse events that were reported included transient ischaemic attack, seizure, asymptomatic subdural haematoma/hygroma, urinary tract infection, sepsis, pneumonia, hyperglycaemia, neutrophilia, shingles, ischaemic stroke, cellulitis, muscle cramps, fracture neck femur, and peripheral vascular disease (89). However, these side effects were attributed to the procedure rather than cell therapy.…”
Section: Clinical Applications Of Mscsmentioning
confidence: 99%
“…This route of administration has become even more relevant due to the widespread use of endovascular treatment methods in acute stroke patients [ 23 ], despite this procedure requiring technical precision due to the risk of cerebral embolism [ 24 ]. Intravenous administration (IV) has also shown therapeutic efficacy and is the most commonly used, because it is less invasive, has minimal risk of adverse events, can be easily applied multiple times, and is suitable even for patients in critical clinical conditions [ 20 , 25 , 26 , 27 ]. Finding the optimal route of transplantation, as well as timing and the dosage of cells, is a challenging task due to the poor understanding of the exact mechanisms of MSCs’ action.…”
Section: Introductionmentioning
confidence: 99%